Brønsted basic TMMM-hydrotrope combined catalytic system for the synthesis of diverse dihydropyranochromenes in water at ambient temperature - Rajmane, Archana; Jadhav, Aishwarya; Patil, Nita; Kumbhar, Arjun (New Journal of Chemistry, 2025)
This work describes the synthesis of a range of bioactive chromenes using a solid Br & oslash;nsted organic base called `tris(morpholinomethyl)mesitylene' (TMMM). TMMM was obtained in high yields by treating tris(bromomethyl)mesitylene (TBMM) with morpholine in the presence of K2CO3 in acetonitrile at RT. It was characterized using 1H NMR and 13C NMR spectroscopy. We developed a Br & oslash;nsted base hydrotrope combined catalytic system (BBHC) by combining TMMM and a hydrotrope (sodium p-toluene sulphonate: NaPTS) for the cascade-type Knoevenagel-Michael addition reactions of various aldehydes and malononitrile with kojic acid, 4-hydroxy coumarin, dimedone, and lawsone in water. The methodology offers diversity-oriented synthesis (DOS) of dihydropyranochromenes in high yields. The BBHC catalytic system showed at least four times recyclability without appreciable loss of its activity. TMMM is an odorless, solid organic base that can be easily handled and is resistant to air and moisture. As TMMM is a solid base, it can reduce evaporation losses, improve safety and allow its easy recovery and reuse. TMMM acts as a powerful Br & oslash;nsted base that activates reactants, while an aqueous solution of NaPTS acts as a hydrotrope that increases the solubility of organic compounds in water.

DABCO dicationic ionic solid supported polymer (DDIS@PS) mediated synthesis of diverse 2-amino-4H-chromenes and xanthenes: a cascade Knoevenagel-Michael approach - Rajmane, Archana; Patil, Nita; Patil, Anuradha; Kamble, Sumit; Kumbhar, Arjun (New Journal of Chemistry, 2025)
This work documented the synthesis of diverse bioactive polysubstituted 2-amino-4H-chromenes using a DABCO dicationic ionic solid (DDIS) supported on Merrifield resin (DDIS@PS) as a catalyst. The catalyst is characterized by FT-IR, SEM-EDX, and TGA analysis. The resulting PS contains supported DABCO units with free tertiary nitrogen functionality on their external surface. The catalyst effectively catalyzed cascade Knoevenagel-Michael addition reactions of various aldehydes and active methylene compounds (malononitrile and phenyl sulfonyl acetonitrile) with dimedone, yielding good to excellent results in water or ethanol at room temperature or 78 degrees C. The time required for the reaction of phenyl sulfonyl malononitrile is comparatively very high compared to malononitrile. The synthesis of bis-dimedone derivatives and 1,8-dioxo-octahydro-xanthenes was also achieved in both solvents at RT and 78 degrees C, with high yields. The catalyst demonstrated greater efficiency and maintained its activity over at least five cycles.

Harnessing DABCO ionic salts for synthesis of heterocycles via multi-component reactions - Rajmane, Archana; Narande, Poonam; Patil, Nita; Kumbhar, Arjun (Chemical Papers, 2025)
The review article discusses the advancements in synthesis and applications of acidic, basic, and neutral 1,4-diazabicyclo[2.2.2]octane (DABCO) ionic salts in multi-component reactions. Compared to imidazolium-based ionic salts, the number of DABCO-based ionic salts is significantly lower. Recently, there has been increasing focus on these salts due to their selective salt formation capabilities. A significant challenge lies in the limited availability of physical data regarding DABCO-based ionic salts; hence, most of them are not ionic liquids. While many of these salts could be reused several times with only a minimal reduction in their catalytic effectiveness, there is a significant limitation in the availability of DABCO-based salts.
Keywords: 1; 4-Diazabicyclo[2.2.2]octane; Ionic salts; Multi-component reactions; Recyclability